Kecenderungan dan Faktor Penyebab Deforestasi di Way Pemerihan, Taman Nasional Bukit Barisan Selatan, Lampung Barat - Suyadi, Suyadi; Gaveau, David Luc Andre (JURNAL BIOLOGI INDONESIA, 2006)
ABSTRACTTrend and Causal Factor of Deforestation in Way Pemerihan, Bukit BarisanSelatan National Park, West Lampung. Deforestation of low land tropical forestis one of the greatest threats to biodiversity in Bukit Barisan Selatan National Park(BBSNP), where this area is the third-largest protected area on Sumatra. Our study is thefirst in BBSNP as integrate between remote sensing and socio-economic survey to demonstratethat the area and rate of forest loss in Way Pemerihan (Cawangaro andSumbersari). The data demonstrated that deforestation activity has been started since1965 in Cawangaro and 1977 in Sumbersari. Forest cover of 1.232ha had already beenlost by deforestation activity, i.e: 579 ha in Cawangaro and 653ha in Sumbersari. Forestloss is increasingly by average rate of 1.2%/year (0.28m2/minute) in the meantime averagerate of regeneration only 0.09%/year. The highest increased of deforestation hasoccurred after politics reformation in 1998. The result of socio-economic survey demonstratedtwo causal factor include internal factor and external factor. Internal factor that islandlessness, price of outside BBSNP land is relatively high and not productive becauseof that low production. External factor of the processes which drives farmer to deforestationis social gap to illegal logging activity, declined of BBSNP forest control and lawenforcement capacity, and boundary conflict between BBSNP with traditional lands.Political reformation forms is the basis for increase external factor.Keywords: Forest loss, satellite imagery, landscape, Illegal logging